The Implementation and Impact of the English Area on Students’ Speaking Skills at Vocation High School - Putri Mansur; A. Musafir Rusyaidi; Yuyun Ruqiyyat Said (Universitas Islam Negeri Palopo, 2026)
This study examines the implementation of the English Area program in improving the speaking skills of tenth-grade students at SMKN 5 Kolaka Utara. Speaking skills, particularly fluency and pronunciation, remain a challenge for many vocational high school students due to limited opportunities to use English in real communication. This study aims to describe the implementation of the English Area program and its contribution to the development of students' speaking skills. This study employed a descriptive qualitative method. Data were collected through classroom observations, interviews with English teachers and students, as well as documentation of the English Area activities. The results showed that the English Area program was implemented through four stages: preparation, implementation, observation, and evaluation. The program includes activities such as Morning Vocabulary, Object Labeling, Daily Conversation Practice, and Warm-up Speaking. The findings indicate that the English Area program successfully created an English-speaking environment that encouraged students to use English more confidently in daily interactions. Students demonstrated a gradual improvement in speaking fluency, characterized by an increased willingness to communicate, reduced hesitation when speaking, and the ability to spontaneously use simple English expressions. Improvement in pronunciation was also evident through teacher modeling, repetitive practice, corrective feedback, and the students' ability to perform self-correction. Although the students' speaking ability is still limited to the use of simple expressions, the program provides a positive contribution to enhancing their confidence and communication skills. Thus, the English Area program can be considered successful in improving students' speaking skills, particularly in the aspects of fluency and pronunciation, and serves as a beneficial strategy for building English communication skills within a vocational high school environment.